Objective assessment of Myringotomy and tympanostomy tube insertion: A prospective single‐blinded validation study. (26th October 2015) - Schwartz, Joseph; Costescu, Adrian; Mascarella, Marco A.; Young, Meredith E.; Husein, Murad; Agrawal, Sumit; Roth, Kathryn; Doyle, Philip C.; Nguyen, Lily H. P.
Abstract : Objectives/Hypothesis: Despite the transition to competency‐based education in surgery, few standardized assessment tools exist in otolaryngology training. In particular, myringotomy and tympanostomy tube insertion (M+T) is a common surgical procedure with few validated assessment tools available. Our objectives were to develop an objective structured assessment of operative skills in M+T and to provide validity evidence for the developed assessment tool within otolaryngology training. Study Design: Prospective study involving the evaluation of an assessment tool. Methods: Through consultation with a panel of experts in otolaryngology and medical education we developed a Task‐Specific Checklist and Global Rating Scale for M+T. Postgraduate year 2 junior residents, postgraduate year 3 senior residents, and attending otolaryngologists were video recorded performing M+T at a tertiary care pediatric hospital. The videos were subsequently reviewed and independently evaluated by three blinded raters from an unaffiliated academic institution. Results: The average score of junior residents, senior residents, and attending otolaryngologists using the Task‐Specific Checklist was 21.7/30 (±7.1), 26.3/30 (±3.5), and 27.3/30 (±6.2), respectively ( P = .04). For the Global Rating Scale, the scores for junior residents, senior residents, and attending surgeons were 27.7/50 (±11.2), 34.5/50 (±9.5), and 45.1/50 (±4.6), respectively ( P < .001). The inter‐rater and intrarater reliability were both above 0.88. Conclusions: The Task‐Specific Checklist and Global Rating Scale for M+T appear reliable, with validity evidence supporting their use in otolaryngology training. Level of Evidence: NA Laryngoscope, 126:2140–2146, 2016